GAMBARAN PENGETAHUAN KELUARGA PASIEN TENTANG LATIHAN RANGE OF MOTION (ROM) PADA PASIEN STROKE: SISTEMATIK LITERATURE REVIEW (Politeknik Kesehatan Kemenkes Bandung, 2020)
Stroke is the third most common cause of death. Deaths reach 160,000 per year. Riskesdas data (2018) shows the prevalence of stroke rose from 7% to 10.9%. Rehabilitation given to stroke patients is with Range of motion (ROM) exercises. Family knowledge about ROM is very important to increase family knowledge in order to help patients to do ROM. This study aims to determine the level of family knowledge about ROM exercises in the families of stroke patients. The research method used is descriptive method, with a literature review design. The results showed that the patient's family knowledge about ROM exercise was in the poor category of 43.1%, the understanding of the patient's family about the goals and principles of Range of Motion (ROM) exercise was included in the inadequate category, with the characteristics of respondents based on age most in the adult category as much 52.6%, the highest number of junior high school education was 41.3%, and the highest status of work was not working as much as 50.6%. So it was concluded that the patient's family knowledge about ROM exercises was in the poor category of 43.1%. For this reason it is recommended to nurses and health services to better educate the patient's family about the importance of ROM exercises in stroke patients. Keywords: Stroke, ROM, Knowledge, Family